2019
DOI: 10.2147/cia.s212852
|View full text |Cite
|
Sign up to set email alerts
|

<p>Utilization, effect, and benefit of the individualized Meeting Centers Support Program for people with dementia and caregivers</p>

Abstract: PurposeThere are few interventions on an individual basis to support community-dwelling people with dementia to continue to fulfill their potential in society and to support their informal caregivers via e-Health. This study explored the effectiveness of the individualized Meeting Centers Support Program (iMCSP) consisting of DemenTalent (people with dementia work as volunteers in a society based on their talents), Dementelcoach (telephone coaching), and STAR e-Learning for caregivers, compared to regular MCSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 41 publications
2
45
0
Order By: Relevance
“…These correspond to small to large effect sizes, respectively, when compared to Cohen’s suggested benchmarks [ 38 ]. Previous evaluations of interventions implemented in the Netherlands to improve social health in dementia have also found moderate to large effect sizes, with respect to similar outcome measures [ 39 , 40 ]. Whilst both pilot studies also revealed small between group differences with respect to a number of outcomes, this trial will not be powered to detect small effects of the intervention.…”
Section: Trial Designmentioning
confidence: 88%
See 2 more Smart Citations
“…These correspond to small to large effect sizes, respectively, when compared to Cohen’s suggested benchmarks [ 38 ]. Previous evaluations of interventions implemented in the Netherlands to improve social health in dementia have also found moderate to large effect sizes, with respect to similar outcome measures [ 39 , 40 ]. Whilst both pilot studies also revealed small between group differences with respect to a number of outcomes, this trial will not be powered to detect small effects of the intervention.…”
Section: Trial Designmentioning
confidence: 88%
“…Other randomized controlled trials evaluating the effectiveness of technology for social health in dementia that we are aware of, have experienced drop-out rates from baseline to three-month follow-up of around 20% [ 41 , 42 ]. We are also aware of recently-conducted RCTs involving community-dwelling participants with dementia in the Netherlands, one of which reported a drop-out rate of 12% after three months and the other reported a dropout rate of 35% after six months [ 39 , 43 ]. A recent review of web-based brain health interventions designed for healthy adult participants identified trials which reported drop-out after various periods of time, with rates ranging from 2 to 52% [ 44 ].…”
Section: Trial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…However, van Mierlo et al did not report how the increase in feelings of competence was associated with improvements in medication management or coping with behavioral changes in PwD. This could be partly due to the fact that a small proportion of ICs receiving Dementelcoach reported to have received new information or practical support [39].…”
Section: • Resultsmentioning
confidence: 98%
“…As part of this work placement, they can carry out activities that allow them a prolonged and more complete utilization of their own abilities. 129 This new approach is expected to have positive effects on the patients' health and well-being.…”
Section: Resultsmentioning
confidence: 99%